RAPID METHOD FOR DETERMINATION OF NANO SURFACE AREA OF ARECANUT SHELL DERIVED ACTIVATED CARBON BY IODINE ADSORPTION NUMBER - A. S. Jadhav,; G. T. Mohanra,; S. Mayadev,; A. N. Gokarn, (Academic Scientific Journal of Chemistry, 2018)
Activated carbon is the most versatile and commonly used adsorbent. Activated carbon is prepared for 5e+10ng , 1e+11ng, and 3e+11ng batch size. Impregnation ratio maintained is 1:1,2:1,3:1,4:1.Nano activated carbon from arecanut shell is derived. Particles size diameter maintained to 53000 nm. In this study the specific surface area determination of activated carbon by means of the low-temperature argon adsorption (the BET method) is compared with the measurement of the surface area based on the adsorption of I2 from the aqueous KI solution. The iodine adsorption number for the BET surface area is calculated. It is predicted iodine adsorption number SIN method can be used for a quick estimation of the structure development of porous carbonaceous materials.